C is the awnser to that question
Answer:
Option C ![-6](https://tex.z-dn.net/?f=-6%3Cx%5Cleq%20-3)
Step-by-step explanation:
we have
![21\leq -3(x-4)](https://tex.z-dn.net/?f=21%5Cleq%20-3%28x-4%29%3C30)
The compound inequality can be divided into two inequality
-----> inequality A
----> inequality B
Solve inequality A
![21\leq -3x+12](https://tex.z-dn.net/?f=21%5Cleq%20-3x%2B12)
![9\leq -3x](https://tex.z-dn.net/?f=9%5Cleq%20-3x)
Divide by -3 both sides
when you multiply or divide both sides of an inequality by a negative number, you must reverse the inequality symbol
![-3\geq x](https://tex.z-dn.net/?f=-3%5Cgeq%20x)
Rewrite
![x\leq -3](https://tex.z-dn.net/?f=x%5Cleq%20-3)
The solution of the inequality A is the interval (-∞,-3]
Solve the inequality B
![-3x+12](https://tex.z-dn.net/?f=-3x%2B12%3C30)
![-3x](https://tex.z-dn.net/?f=-3x%3C18)
Divide by -3 both sides
when you multiply or divide both sides of an inequality by a negative number, you must reverse the inequality symbol
![x>-6](https://tex.z-dn.net/?f=x%3E-6)
The solution of the inequality B is the interval [-6,∞)
The solution of the compound inequality is
[-6,∞) ∩ (-∞,-3]=(-6,-3]
![-6](https://tex.z-dn.net/?f=-6%3Cx%5Cleq%20-3)
Answer:
its B
Step-by-step explanation:
I just did it